THE ANALYSIS OF FANTASY GENRE'S FORMULA ON HARRY POTTER SERIES - Riza Ambariski (Universitas Gadjah Mada, 2012)
This study aims to discover and analyze the formula of fantasy genre that can be found in the seven books of Harry Potter. This is a qualitative study, focusing the research on the particular literary pieces only. This study uses genre theory as the approach in order to fulfill its objective. Genre theory is commonly used to analyze popular fiction which is appropriate to do formula analysis. As the result of this study, there are at least seven formulas of fantasy genre can be found in the series of Harry Potter. Most of those formulas are regularly appear in fantasy stories, especially in popular fiction.